Democratic Sovereignty and Brexit: A Conversation with Richard Tuck on Political Theory and Practice. Issue 4 (2nd October 2018) - Tuck, Richard; Li, Hansong
ABSTRACT: Richard Tuck is a prominent political theorist and historian of political thought who conducts wide-ranging studies on texts and authors ancient and modern, across disciplines and traditions. A thinker by training and teacher by profession, Tuck has not refrained from intervening in political discourses of our day, such as the question of Britain's withdrawal from the European Union. This conversation with Tuck on political theory and its implication for democratic practice and international politics is conducted by Hansong Li on April 9, 2018 at the University of Cambridge.